Performance of Laboratory Professionals Working on Malaria Microscopy in Tigray, North Ethiopia - Megbaru Alemu; Desalegn Tadesse; Tesfaye Hailu; Wondemagegn Mulu; Awoke Derbie; Tadesse Hailu; Bayeh Abera (Journal of Parasitology Research)
Background. Microscopic analysis of stained blood smear is the most suitable method of malaria diagnosis. However, gaps were observed among clinical laboratory professionals in microscopic diagnosis of malaria. Methods. A cross-sectional study was conducted in December 2015 among 46 laboratory professionals. Data was collected via on-site assessment and panel testing. The slide panel testing was composed of positive and negative slides. The kappa score was used to estimate the agreement between participants and reference reader. Results. The overall agreement between the study participants and the reference reader in malaria detection was 79% (kappa = 0.62). Participating in refresher training on malaria microscopy (Adjusted Odds Ratio (AOR = 7, CI = 1.5–36.3)) and malaria epidemic investigation (AOR = 4.1 CI = 1.1–14.5) had statistical significant association with detection rate of malaria parasites. Conclusion. Laboratory professionals showed low performance in malaria microscopy. Most of the study participants were graded “in-training” in laboratory diagnosis of malaria.